How COVID 19 effect Malaysian paddy industry? Adoption of green fertilizer a potential resolution - Adnan, N. (Springer Science and Business Media B.V., 2021)
The COVID-19 pandemic resulted in more than 4.3 million confirmed cases and more than 2,90,000 deaths worldwide. It has also given rise to fears of an imminent economic crisis and recession. Social distance, self-isolation, and travel restrictions have led to a reduction in the workforce across all economical sectors and have led to a loss of many jobs. Schools have closed down, and the need for commodities and manufactured goods has decreased. On the other hand, the need for medical supplies has increased significantly. The food sector is also facing increased demand as a result of panic buying and storing food products. In response to this global outbreak, we summarize the socioeconomic effects of COVID-19 on the various aspects of the world economy. In Malaysia, the COVID-19 epidemic has checked the resilience of the agriculture sector. Especially the Malaysian paddy industry as country imports 30 of its overall consumption from different parts of the world. The real price of rice triplicating for the consumers, which was alarming for nations in this pandemic situation. The Government of Malaysia introduced the National Agrofood Policy 2011â2020 (NAP4) in 2010 as a guidance document for the implementation of agricultural sector development programs and projects in Malaysia. The NAP4 âs 10-year term is to be finished by the end of 2020. Several sectors demonstrate substantial success after approximately 8Â years of introduction, while the other classes often lag behind the goal and progress quite slowly. Agricultural sector performance is affected by many problems and challenges. In acknowledgment of the poor success of this field, the Ministry of Agriculture and Agri-Based Industry has launched new approaches, policies, and programs that can change the agricultural sector more rapidly. The new direction is aimed at ensuring national food security and boosting farm and revenues. The authorized government agency needs to revise the policy formulation where Malaysia needs to set stages to revolutionize and modernize the rice farming to address the problem faced by the paddy sector in this pandemic situation to adopt GF. In this study, the researcher focuses on the improvisation of the policy to increase the paddy production sustainably. Â© 2020, Springer Nature B.V.